Suspected new syndrome: idiopathic chronic systemic inflammatory dryness – a case report - Samajpaty, Soham (International Journal of Research in Medical Sciences, 2024)
The current article discusses a peculiar and identifies an atypical autoimmune disease termed as the idiopathic chronic systemic inflammatory dryness. In the reported case, the clinical signs are to some extent identical to Sjogren’s syndrome with dry eyes, dry mouth and dry vagina but the biomarkers are negative for it. On the other hand, the biomarker for systemic sclerosis is positive but no clinical signs or symptoms of it were present. The present case also has a probable association with history of toxoplasmosis. The article is of utmost importance in the discourse of development and research of concurrent immunology and understanding of autoimmune diseases.